Non-pharmacologic approaches to treatment of pediatric functional abdominal pain disorders - Chakraborty, Partha Sarathi; Daniel, Rhea; Navarro, Fernando A. (Frontiers in Pediatrics, 2023)
Functional abdominal pain disorders (FAPDs) affect up to 25% of children in the United States. These disorders are more recently known as disorders of “brain and gut” interaction. The diagnosis is based on the ROME criteria, and requires the lack of an organic condition to explain the symptoms. Although these disorders are not completely understood, several factors have been involved in the pathophysiology including disordered gut motility, visceral hypersensitivity, allergies, anxiety/stress, gastrointestinal infection/ inflammation, as well dysbiosis of the gut microbiome . The pharmacologic and non-pharmacologic treatments for FAPDs are directed to modify these pathophysiologic mechanisms. This review aims to summarize the non-pharmacologic interventions used in the treatment of FAPDs including dietary modifications (low FODMAP diet, gluten and wheat restriction), manipulation of the gut microbiome (neutraceuticals, prebiotics, probiotics, synbiotics and fecal microbiota transplant) and psychological interventions that addresses the “brain” component of the brain-gut axis (cognitive behavioral therapy, hypnotherapy, breathing and relaxation techniques). In addition, this review will also include complementary/alternative medicines as these therapies are commonly used. In a survey conducted at a large academic pediatric gastroenterology center, 96% of patients with functional pain disorders reported using at least 1 complementary and alternative medicine treatment to ameliorate symptoms. Electrical field stimulation interventions like gastric electrical stimulation and percutaneous electrical nerve field stimulation have shown promise in some studies. The paucity of data of most of these therapies underscores the need for large randomized controlled trials to assess their efficacy and superiority compared to other treatments.